Resveratrol, Acetyl-Resveratrol, and Polydatin Exhibit Antigrowth Activity against 3D Cell Aggregates of the SKOV-3 and OVCAR-8 Ovarian Cancer Cell Lines - Simon J. Hogg; Kenny Chitcholtan; Wafaa Hassan; Peter H. Sykes; Ashley Garrill (Obstetrics and Gynecology International)
Resveratrol has aroused significant scientific interest as it has been claimed that it exhibits a spectrum of health benefits. These include effects as an anti-inflammatory and an antitumour compound. The purpose of this study was to investigate and compare any potential antigrowth effects of resveratrol and two of its derivatives, acetyl-resveratrol and polydatin, on 3D cell aggregates of the EGFR/Her-2 positive and negative ovarian cancer cell lines SKOV-3 and OVCAR-8, respectively. Results showed that resveratrol and acetyl-resveratrol reduced cell growth in the SKOV-3 and OVCAR-8 in a dose-dependant manner. The growth reduction was mediated by the induction of apoptosis via the cleavage of poly(ADP-ribose) polymerase (PARP-1). At lower concentrations, 5 and 10 µM, resveratrol, acetyl-resveratrol, and polydatin were less effective than higher concentrations, 50 and 100 µM. In SKOV-3 line, at higher concentrations, resveratrol and polydatin significantly reduced the phosphorylation of Her-2 and EGFR and the expression of Erk. Acetyl-resveratrol, on the other hand, did not change the activation of Her-2 and EGFR. Resveratrol, acetyl-resveratrol, and polydatin suppressed the secretion of VEGF in a dose-dependant fashion. In the OVCAR-8 cell line, resveratrol and acetyl-resveratrol at 5 and 10 µM increased the activation of Erk. Above these concentrations they decreased activation. Polydatin did not produce this effect. This study demonstrates that resveratrol and its derivatives may inhibit growth of 3D cell aggregates of ovarian cancer cell lines via different signalling molecules. Resveratrol and its derivatives, therefore, warrant further in vivo evaluation to assess their potential clinical utility.